Divine Proportion in edentulous subjects: Assessment before and after complete dentures - Costa, Carolina Bacci [UNESP]; Ono, Evelise; Henriques, João César Guimarães [UNESP]; Medici-Filho, Edmundo [UNESP]; De Moraes, Mari Eli Leonelli [UNESP]; De Melo Castilho, Julio Cezar [UNESP] (My University, 2012)
Purpose: The aim of this study was to evaluate ratios between bone structures of the skull and the face of edentulous subjects, before and after prosthodontic treatment with complete dentures. Methods: New complete dentures were fabricated by conventional methods, and subjects (n=30) were evaluated cephalometrically before and after the new prosthesis. Using the same cephalometric unit, standardized lateral cephalometric headfilms were made on each subject in two times: the first without the complete dentures, in the rest position of the mandible, and the second with the new one in place, in maximal intercuspation. The lateral cephalometric x-rays were digitized and analyzed using computer software Radiocef Studio 2 - Radiomemory (Belo Horizonte, Minas Gerais, Brazil). The means of 7 different ratios were statistically analysed by paired t-test and Student's t-test, and compared with the golden number 1,618. Results: There were no statistically significant results in ratios orbitale-menton/condilliongonion, pogonion-opisthion/orbitale-menton and pogonion-opisthion/posterior nasal spineopisthion, before and after prosthodontic treatment. The ratios orbitale-menton/anterior nasal spine-posterior nasal spine, orbitale-menton/nasion-anterior nasal spine, orbitale-menton/opisthion-nasion and nasion-menton/anterior nasal spine-menton were different statistically. Conclusion: The ratio nasion-menton/anterior nasal spine-menton wich relates two important segments, the total anterior facial height and the lower anterior facial height, was closer to the golden number after news complete dentures. Copyright: © 2012 Costa et al.; licensee EDIPUCRS.
Keywords: Cephalometry; Complete denture; X-rays